HEALTH OF WOMEN OVER FIFTY YEARS OLD PRACTITIONERS OF REGULAR PHYSICAL EXERCISE, BOTUCATU – SP (Fiep Bulletin - online, 2013)
We observed a policy of encouraging physical activity, note that sedentary lifestyle has affected various social levels and age groups. The setting seems more negative than in women, the elderly and people with lower education. Thus, this study aims to estimate the prevalence of health problems among physically active women above fifty years in two sports institutions in Botucatu, São Paulo. We used a cross-sectional study subsidized by questionnaires. Among the results, we highlight older women in N2 (p
Keywords: Physical activity; women; prevalence; health; disease.